International actors and traditional justice in Sub-Saharan Africa :policies and interventions in transitional justice and justice sector aid - Brems, Eva (2015)
Due to a number of important differences between transitional justice and justice sector aid, this book explored how international actors address ‘traditional justice’ in these fields in two distinct parts, which has led to separate analyses. Justice sector aid is often part of broader development cooperation programmes, which may or may not take place in a ost-conflict country. Transitional justice processes are part of conflict-related international interventions, such as peacebuilding programmes, which are often implemented before the wheels of more longterm development cooperation programmes are set in motion. Chronologically speaking, both kinds of programmes – support for transitional justice and justice sector aid – often do not run parallel, although there can be overlaps. It also turns out that the international actors are not necessarily the same. Although in principle the same donor countries are involved, justice sector aid is often provided by bilateral or multilateral development organisations, while transitional justice interventions are more often – but certainly not exclusively – initiatives of specific agencies aimed at post-conflict reconstruction, which are established by several donor countries. Although respect for human rights is heavily emphasised in both domains, policy and interventions regarding transitional justice also need to take international norms regarding the criminal prosecution of international crimes into account. In spite of these differences, this concluding chapter formulates a number of mutual findings and recommendations. First, it discusses common elements at the level of policies, then it identifies a number of trends regarding interventions, and finally it examines the way in which linternational actors handle the tension between traditional justice and human rights